THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ON TAX AGGRESSIVENESS (A RESEARCH ON MANUFACTURING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE FROM 2015-2017) - Aditya, Muhamad Diva (Jurnal Ilmiah Mahasiswa FEB, 2019)
This research aims to examine the effect of corporate social responsibility (CSR) disclosures towards corporate tax aggressiveness. The independent variable used in this research is social responsibility disclosure. While the dependent variable is the effective tax rates proxy. This present research is a replication of the research conducted by Lanis and Richardson (2012) which is done by involving 151 manufacturing companies listed on the Stock Exchange in 2015-2017 as the research population. The research sample was selected by purposive sampling method and obtained 14 companies per year that met the criteria for 3 years period. The data were analyzed using a simple linear regression analysis model. The results of the research indicate that the disclosure of CSR does not have any effect on the tax aggressiveness of a company. Keywords: corporate social responsibility and tax aggressiveness